Leonidas Karakatsanis and Nikolaos Papadogiannis, eds., The Politics of Culture in Turkey, Greece and Cyprus: Performing the Left Since the Sixties - Rappas, Alexis (Historein, 2020)
Review of Leonidas Karakatsanis and Nikolaos Papadogiannis, eds., The Politics of Culture in Turkey, Greece and Cyprus: Performing the Left Since the Sixties. London: Routledge, 2017. 321 pp.